2022
DOI: 10.1021/jacs.2c01089
|View full text |Cite
|
Sign up to set email alerts
|

Can Brønsted Photobases Act as Lewis Photobases?

Abstract: Dative bonding or Lewis acid–base chemistry underpins a large number of chemical phenomena in a variety of fields, such as catalysis, metal–ligand interactions, and surface chemistry. Developing light-controlled Lewis acid–base interactions could offer a new way of controlling and understanding such phenomena. Photoinduced proton transfer, that is, excited-state Brønsted acidity and basicity, has been extensively studied and applied. Here, in direct analogy to excited-state Brønsted basicity, we show that exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Voegtle and Dawlaty investigated the strength of Lewis adducts created by combining BF 3 to a series of quinoline derivatives, acting as photoactive Lewis bases . The focus of this work was not primarily on the photochemistry of the Lewis adducts but on how different quinoline-based Lewis bases could affect the strength of the B–N bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voegtle and Dawlaty investigated the strength of Lewis adducts created by combining BF 3 to a series of quinoline derivatives, acting as photoactive Lewis bases . The focus of this work was not primarily on the photochemistry of the Lewis adducts but on how different quinoline-based Lewis bases could affect the strength of the B–N bond.…”
Section: Resultsmentioning
confidence: 99%
“…Voegtle and Dawlaty investigated the strength of Lewis adducts created by combining BF 3 to a series of quinoline derivatives, acting as photoactive Lewis bases. 77 The focus of this work was not primarily on the photochemistry of the Lewis adducts but on how different quinoline-based Lewis bases could affect the strength of the B–N bond. A first observation from this work is that all quinolines showed an increased bonding affinity for BF 3 when the adduct was in its first excited electronic state.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that the strength of classic Lewis pairs is modified upon light excitation. 12 Studying the interfacial Lewis interactions is important in electrochemistry. However, Lewis bonding is often convoluted with a range of complex phenomena at the surface, including poor characterization of surface sites and geometries, involvement of the band structure of the solids, difficulty in measurement of partial electrosorption valency of the adsorbates, and finally competing reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Carino et al have demonstrated formation of BF 3 –quinoxiline adducts from a LiBF 4 electrolyte and subsequent modification of redox properties of the Lewis adduct. Recent work has shown that the strength of classic Lewis pairs is modified upon light excitation …”
Section: Introductionmentioning
confidence: 99%
“…Redox-active organic molecules are used in a wide variety of applications, ranging from energy storage, use as photochemical sensitizers, as homogeneous (electro)catalysts, and in biomedical applications. [1][2][3][4][5][6] The generation of charged organic molecules facilitates their solubility in aqueous and nonaqueous solvents. We are particularly interested in boron compounds.…”
Section: Introductionmentioning
confidence: 99%